GRAMMATICAL AND LEXICAL COHESION ANALYSIS OF TRUMP’S SPEECH UPON SOLEIMANI ASSASSINATION - Vidya Mandarani (BASIS (Bahasa dan Sastra Inggris), 2020)
This study specifically examined the grammar and lexical cohesion of a speech from one of the controversial figure, Donald Trump, regarding with a current reckless assassination upon Iran’s highest general, Qasem Soleimani, in early 2020. Such investigation required the use of textual analysis of a designated speech from a YouTube video, which transcripted further be thoroughly examined. The results showed that Trump positively justified his action while negatively claim the opposite of his addressee. This was shown with the most frequent form of cohesion for the grammatical section is the reference with 65 pieces of evidence, as well as near-synonym and repetition with only 9 evidence for lexical section. While the least form is the conjunction with 23 evidence, also both synonym and general word with only 1 evidence. This also highlighted that the use of some cohesion features displays a different aim and effect. All in all, this study presented a theoretical implication, where all elements of a related proper speech entailed the use of grammatical and lexical cohesion altogether.